Digital tax compliance in India: A data-driven analysis of income tax return filings (2021–2026) - Krishna, V. Murali; Gowda, A. R. Ashok; Gunakala, Ravikumar (The International tax journal, 2026)
This study investigates the dynamics of digital tax compliance in India by analyzing Income Tax Return (ITR) filings from 2021 to 2026 using secondary data. Advanced analytical techniques such as time series modeling, regression analysis, hypothesis testing, and ARIMA forecasting were employed using tools including Python, R, SPSS, and Power BI. The results reveal a steady increase in ITR filings with a CAGR of 7.47 per cent, indicating sustained growth in compliance. Regression and correlation analysis confirm a strong positive relationship between digital adoption and filing behavior, while hypothesis testing establishes statistical significance (p < 0.05). Forecasting results further indicate a stable upward trajectory, suggesting maturity in India’s digital tax ecosystem. Despite high processing efficiency levels above 95 per cent, a marginal decline indicates growing pressure on administrative systems. The study concludes that digitalization has significantly improved tax compliance, though backend efficiency and taxpayer awareness remain critical areas for improvement.